Дослідження застосування методів пост-квантової криптографії для розподілених систем авторизації - Нікітченко, Б. Ю. (ХНУРЕ, 2023)
This work discusses quantum computers and their impact on modern cryptography. It explains how quantum computers can exponentially speed up decryption, which is a serious threat to encryption systems based on algorithms such as RSA, discrete logarithm, and Diffie-Hellman. Post-quantum cryptography (PQC) is suggested as a solution, and several PQC solutions such as lattice-based cryptography, code-based cryptography, and hash-based signatures are proposed. The work also mentions quantum key distribution (QKD) as another solution to the existing cryptography problem.